1994
DOI: 10.1111/j.1532-5415.1994.tb07490.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Presence of a Third Person on the Physician‐Older Patient Medical Interview

Abstract: The presence of a third person in the medical encounter changes the interactional dynamics of older patient medical interviews and may influence the development of a trusting and effective physician-older patient relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 13 publications
2
83
3
Order By: Relevance
“…The scarce research on multi-party medical interactions within the setting of pediatrics [34][35][36], geriatrics [37], dietary counseling [38] and the general practitioner's surgery [39,40] showed that the mere presence of a third person changes the dynamics of the medical interaction, no matter how small the third person's conversational contribution to the actual visit. After all, in attending a health care provider, patients have their agenda (needs and expectations) but so have the persons accompanying the patient.…”
Section: Beyond the Dialoguementioning
confidence: 99%
“…The scarce research on multi-party medical interactions within the setting of pediatrics [34][35][36], geriatrics [37], dietary counseling [38] and the general practitioner's surgery [39,40] showed that the mere presence of a third person changes the dynamics of the medical interaction, no matter how small the third person's conversational contribution to the actual visit. After all, in attending a health care provider, patients have their agenda (needs and expectations) but so have the persons accompanying the patient.…”
Section: Beyond the Dialoguementioning
confidence: 99%
“…Estimates vary as to the frequency of family members in medical visits but studies have found that companions attend between 20% and 37% of older adults' medical visits. [3][4][5][6] Researchers have documented both negative 5,7 and positive 6,8 effects associated with accompanied visits. For example, Green and associates 7 stated that individual patients get less attention from physicians when family members are present in the session.…”
mentioning
confidence: 99%
“…However, Greene et al (35) found that when a relative or friend accompanied the older patient to a consultation, the patient was less likely to ask questions, less assertive and expressive and less likely to be involved in the decision-making process.…”
Section: Role Of a Family Member/friend In Communication Processmentioning
confidence: 99%